2022
DOI: 10.3389/fphar.2022.851940
|View full text |Cite
|
Sign up to set email alerts
|

Interleukins 4 and 13 in Asthma: Key Pathophysiologic Cytokines and Druggable Molecular Targets

Abstract: Interleukins (IL)-4 and -13 play a pivotal role in the pathobiology of type-2 asthma. Indeed, IL-4 is crucially involved in Th2 cell differentiation, immunoglobulin (Ig) class switching and eosinophil trafficking. IL-13 cooperates with IL-4 in promoting IgE synthesis, and also induces nitric oxide (NO) production, goblet cell metaplasia and fibroblast proliferation, as well as elicits contractile responses and hyperplasia of airway smooth muscle cells.IL-4 and IL-13 share common signaling pathways, activated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 93 publications
1
35
0
Order By: Relevance
“…The daily dose of prednisone decreased by -5.00 mg (from -12.50 to 0.00) in patients without CRSwNP and -12.5 mg (from -25.00 to 0.00) in subjects with CRSwNP, respectively (p < 0.05) (Figure 6B). The increase in ACT score was 7 points (4-10) and 7 points (4)(5)(6)(7)(8)(9)(10)(11) in patients without or with CRSwNP, respectively (p = 0.422) (Figure 6C). The mean increase in FEV 1 was 0.15 L (-0.01-0.49) in patients without CRSwNP, and 0.24 L (0.01-0.69) in subjects with CRSwNP; this difference was not statistically significant (p = 0.138) (Figure 6D).…”
Section: Efficacy Of Dupilumab In Patients With or Without Crswnpmentioning
confidence: 95%
“…The daily dose of prednisone decreased by -5.00 mg (from -12.50 to 0.00) in patients without CRSwNP and -12.5 mg (from -25.00 to 0.00) in subjects with CRSwNP, respectively (p < 0.05) (Figure 6B). The increase in ACT score was 7 points (4-10) and 7 points (4)(5)(6)(7)(8)(9)(10)(11) in patients without or with CRSwNP, respectively (p = 0.422) (Figure 6C). The mean increase in FEV 1 was 0.15 L (-0.01-0.49) in patients without CRSwNP, and 0.24 L (0.01-0.69) in subjects with CRSwNP; this difference was not statistically significant (p = 0.138) (Figure 6D).…”
Section: Efficacy Of Dupilumab In Patients With or Without Crswnpmentioning
confidence: 95%
“…The upregulation of various molecules, including cytokines, chemokines, and adhesion molecules, has been reported in the pathogenesis of asthma [ 36 , 51 , 52 ] and in experimental models of inflammatory lung diseases, including AA [ 53 , 54 , 55 ]. Accumulated evidence has indicated that the activation of NF-κB plays a pivotal role in the expression of inflammatory molecules in lung epithelial cells and macrophages [ 5 , 13 , 15 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many cases of asthma are also eosinophilic, often with the extent of the eosinophilia determining disease severity ( Bakakos et al, 2019 ). The Th2 cytokines IL-5, IL-4 and IL-13 have all been linked to eosinophil trafficking or the activation of adjacent signalling pathways such as the IgE cascade responsible for Th2 lymphocyte production thus encouraging further migration of eosinophils ( Fulkerson and Rothenberg, 2013 ; Pelaia et al, 2022 ). In addition to increases in eosinophils, many other immune cells are also upregulated within inflamed airways including dendritic cells, basophils and mast cells which may also have antigen-presenting roles alongside their effector roles ( Kim et al, 2010 ).…”
Section: Allergic Asthma—symptoms Disease Course and Pathological Mec...mentioning
confidence: 99%